Improving Interdisciplinary Communication With Standardized Cyber Security Terminology: A Literature Review - Robert Ramirez (IEEE Access, 2016)
The growing demand for computer security, and the cyberization trend, are hallmarks of the 21st century. The rise in cyber-crime, digital currency, and e-governance has been well met by a corresponding recent jump in investment in new technology for securing computers around the globe. Business and government sectors have begun to focus effort on comprehensive cyber security solutions. With this effort has emerged a need for greater collaboration between research and industry fields. Despite much effort, there is still too little cross-disciplinary collaboration in the realm of computer security. This paper reviews the new trends, contributions, and identifiable limitations in cyber security research. We argue that these limitations are due largely to the lack of interdisciplinary cooperation required to address a problem that is clearly multifaceted. We then identify a need for further refinement of standard cyber security terminology to facilitate interdisciplinary cooperation, and propose guidelines for the global Internet multistakeholder community to consider when crafting such standards. We also assess the viability of some specific jargon, including whether cyber should be a separate word when used as a descriptor (e.g. cyber-crime or cybercrime), and conclude with recommendations for terminology use when writing papers on cyber security or the new broader field of all things relating to cyberspace, which has recently been dubbed Cybermatics, a term we also examine and propose alternatives to. By furthering the effort to standardize cyber security terminology, this paper lays groundwork for cross-disciplinary collaboration, interaction between technical and nontechnical stakeholders, and drafting of universal Internet governance laws.